2020
DOI: 10.1021/acsnano.0c01924
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Fluorescence Mechanism of Carbon Dots with Sub-Single-Particle Resolution

Abstract: Unlike quantum dots, photophysical properties of carbon dots (CDs) are not strongly correlated with particle size. The origin of CD photoluminescence has been related to sp2 domain size and the abundance of oxidized surface defects. However, direct imaging of surface-accessible spatially localized oxidized defects is still lacking. In this work, solvothermal-synthesized CDs are fractionated into different colors by polarity-based chromatography. We then study the mechanism of CD fluorescence by directly imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
134
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 78 publications
8
134
0
Order By: Relevance
“…Fu and coworkers proposed that PAHs of different sizes within the carbogenic core account for the excitation-dependent photoluminescence (PL) of CQDs [8]. e dependence of PL on the excitation wavelength is wildly observed in CQDs [6,9,10], even on a single CQD [11], and it could be attributed to the existence of multiple emitters within CQDs [12,13], especially to MFs [14][15][16]. On the contrary, Wang [17] and Yuan [18] groups reported that the emission spectra of CQDs, except for emission intensity, are independent on the excitation wavelength, probably due to simplicity in CQDs' structure [18].…”
Section: Introductionmentioning
confidence: 99%
“…Fu and coworkers proposed that PAHs of different sizes within the carbogenic core account for the excitation-dependent photoluminescence (PL) of CQDs [8]. e dependence of PL on the excitation wavelength is wildly observed in CQDs [6,9,10], even on a single CQD [11], and it could be attributed to the existence of multiple emitters within CQDs [12,13], especially to MFs [14][15][16]. On the contrary, Wang [17] and Yuan [18] groups reported that the emission spectra of CQDs, except for emission intensity, are independent on the excitation wavelength, probably due to simplicity in CQDs' structure [18].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, after the separation, both the types of CDs show similar absorption bands in the visible range, distinct from the chemical groups or structures forming the CDs, in agreement with [24]. However, the possibility of safely inferring the exact origin of the electronic transitions giving rise to these bands is not trivial: similar absorption bands above 300 nm are often related to the n-π * transitions of the surface-related chemical groups of the CDs that form a system of multiple discrete energy states [29,43,44,[47][48][49]. However, other reports [24,25,50,51] ascribe them to the π-π* and n-π* transitions, respectively, of the characteristic interconnected heteroaromatic units of the CDs.…”
Section: O-cd Synthesismentioning
confidence: 75%
“…The UV-Vis absorption spectra ( Figure 1b) clearly display a peak at around 260 nm, and two faint bands at 360 and 420 nm. In the literature, for CDs synthesized with diverse approaches, the signal below 300 nm in the absorption spectrum is commonly ascribed to the characteristic π-π* transitions of the carbogenic cores of the CDs, due to the conjugated sp 2 -carbon domains [27,29,[42][43][44][45]. Moreover, in such a spectral range, the π-π* absorption transitions of the polyheteroaromatic structures derived from pyridinium units of the CPC head-group can also occur.…”
Section: O-cd Synthesismentioning
confidence: 99%
“…Mohsen Kompany-Zareh 1,2* & Saeed Bagheri 1 Exploration in the way of understanding the optical behavior and structure of carbon nanodots has been increased due to their vast application. Their emission dependency on excitation wavelengths is the more prevalent and controversial subject.…”
Section: Perception On Aggregation Induced Multicolor Emission and Emission Centers In Carbon Nanodots Using Successive Dilution Anion Exmentioning
confidence: 99%
“…Since its emersion, fluorescence carbon nanodots (CND) entice the subject of material science, due to their exceptional optical and electronic properties, the availability of precursor materials, and ease of their synthesis [1][2][3][4][5][6][7][8][9][10] . In some cases, CNDs are considered among the quantum dots (QD) which are mainly synthesized by the heavy elements 3,6,9 .…”
Section: Perception On Aggregation Induced Multicolor Emission and Emission Centers In Carbon Nanodots Using Successive Dilution Anion Exmentioning
confidence: 99%